OUTER RETINAL TUBULATION IN BIETTI CRYSTALLINE DYSTROPHY ASSOCIATED WITH THE RETINAL PIGMENT EPITHELIUM ATROPHY. Issue 4 (14th April 2023) - Wang, Yusong; Chen, Jieqiong; Sun, Junran; Li, Tong; Yu, Suqin; Gong, Yuanyuan; Yu, Yang; Wan, Xiaoling; Jia, Huixun; Wu, Jihong; Yuan, Fei; Shen, Xi; et al.
Abstract : Supplemental Digital Content is Available in the Text. We conducted a multicenter, retrospective cohort study to determine the prognostic value of outer retinal tubulation in Bietti crystalline dystrophy. We demonstrated the morphologic characteristics of outer retinal tubulation and found that the progression of retinal pigment epithelium atrophy and vision loss was slower in eyes with outer retinal tubulation than eyes without outer retinal tubulation. Abstract : Purpose: To determine the prognostic value of outer retinal tubulation (ORT) in the eyes of a Chinese cohort with Bietti crystalline dystrophy (BCD). Methods: This retrospective, multicenter cohort study enrolled 42 patients with clinically and genetically diagnosed BCD. Eighty eyes with good-quality images of spectral domain optical coherence tomography were included. Demographic details and clinical data were collected. The characteristics of ORT, including prevalence, location, and morphologic characteristics were analyzed. Results: Forty-two patients with BCD harbored potentially CYP4V2 disease-causing mutations. The mutation spectrum comprised 17 unique variants, 9 of which were novel. Fifty-two of these 80 eyes demonstrated evidence of ORT. The incidence of ORT is significantly higher in Stage 2 than other stages ( P < 0.001). ORT was mainly bilateral and located at the margin of the atrophic area of retinal pigment epithelium (RPE), and dynamically changed with the progressive RPE atrophy. The process of RPE atrophy was slower in eyes with ORT ( P = 0.017), with significantly longer intact RPE width in Stage 3 ( P = 0.024). Eyes with ORT had slower vision loss than eyes without ORT ( P = 0.044). Conclusion: ORT may be a sign of the onset of RPE atrophy in early-stage BCD and may suggest less risk of rapid progression in late-stage BCD.